Cultural Diversity Drives Innovation: Does Institutional Residence Time Impact Behaviors? - Fabrice Gallou; Arnaud Grandeury; GRAHAM JONES (Journal of Innovation Management, 2022)
Innovation activities in large organizations are typically conducted by teams. Previous research noted the positive correlation between innovation performance and the cultural diversity of teams, wherein people from different backgrounds approach problems differently and have differing tolerances for risk. In a long term extension of these studies we aim to determine if these proclivities attenuate over time, as members modify & harmonize their behaviors driven by cultural norms of the organization. In an early read out from this effort, cohorts of innovation team members across several continents and representing six of the ten global cultural clusters completed a series of team analytics and questionnaires. The analytics were derived from cross-cultural communication frameworks which have been utilized to assess how culturally associated values influence behavioral traits. The respondents invited to participate were directly involved in innovation projects either as part of their main function or through membership of a specific innovation team and represented a range of experience levels. Subjects were also invited to offer written commentary on team and organizational culture as it applies to innovation. A definitive trend was uncovered wherein employee service time (in years) correlated with moves from cultural group norms towards more moderated, centrist decision making traits and lowered risk taking appetite. Further, specific indicators which correlate to disruptive ideation and innovation performance softened as a function of service time, independent of cultural origins. Together, this may signal a need for innovation teams to be mindful that balance is maintained with respect to members service time and new team entrants are supported to pursue high-risk high-reward ideas.